PENDEKATAN ERROR CORRECTION MODEL SEBAGAI PENENTU HARGA SAHAM - Kaluge, David (University of Merdeka Malang, 2010)
This research was to find the effect of profitability, rate of interest, GDP, and foreign exchange rate on stockprices. Approach used was error correction model. Profitability was indicated by variables EPS, and ROIwhile the SBI (1 month) was used for representing interest rate. This research found that all variablessimultaneously affected the stock prices significantly. Partially, EPS, PER, and Foreign Exchange rate significantlyaffected the prices both in short run and long run. Interestingly that SBI and GDP did not affect theprices at all. The variable of ROI had only long run impact on the prices.